Cognitive matrices in folktales and contemporary practices of deliberation - Horvat, Marjan (Acta Histriae, 2022)
The aim of the paper is to illuminate how folktales, with their specific conceptualization of universal dilemmas, reflect culture-bound patterns of decision-making in relation to the contemporary socio-political discourse in a given society. In this respect, I perceive folktales firstly as a reflection of embedded cognitive/cultural matrices that determine »cognitive-instrumental rationality«, linked to traditions and cultural norms (Jürgen Habermas). I explore these matrices using a new methodological approach which connects the sociological theory of fairy tales, deliberative democracy and cognitive history. This approach is then applied to the analysis of the conceptualization of dilemmas in three Slovenian folktales (Mojca Pokrajculja, The Ant and the Lazy Cricket, The Bean, the Straw, and the Coal). The analysis asserts correlations between traditionally and culturally conditioned forms of decision-making, and contemporary practices of decision-making / deliberation, thus shedding light on the specifics of national epistemology from a comparative and historicist perspective.
Keywords: deliberativna demokracija; kognitivna zgodovina; kulturna percepcija; ljudske pravljice; študiji primerov; vzorci odločanja